I'm starting to worry about this black box of doom - Pargin, Jason, 1975- (St. Martin's Press, 2024)
"Outside Los Angeles, a driver pulls up to find a young woman sitting on a large black box. She offers him $200,000 cash to transport her and that box across the country, to Washington, DC. But there are rules: He cannot look inside the box. He cannot ask questions. He cannot tell anyone. They must leave immediately. He must leave all trackable devices behind. As these eccentric misfits hit the road, rumors spread on social media that the box is part of a carefully orchestrated terror attack intended to plunge the USA into civil war. The truth promises to be even stranger, and may change how you see the world"--